Learning Ecosystem Material with Project Based Learning (PjBL) Model to Improve Science Process Skills and Student Creativity - Intan Rita Savitri; R. Susanti (Universitas Negeri Semarang, 2024)
This research is a quasi-experiment with a non-equivalent control group design. The samples in this study were X1 and X2 grade students who were determined by cluster purposive sampling. Data collection techniques were carried out by distributing pretest and posttest. Data analysis used in this research is normality test, homogeneity test, independent sample t-test, and n-gain test. The results of this study showed that ecosystem learning with Project Based Learning (PjBL) model can improve science process skills and creativity. The N-Gain test results of science process skills of control class students were 0.30 which was categorized as low and the experimental class was 0.64 which was categorized as moderate. While the N-Gain test of student creativity in the control class was 0.29 which was categorized as low and the experimental class was 0.58 which was categorized as moderate. The conclusion of this research is that learning ecosystem material with the PjBL model can improve students' science process skills and creativity. Suggestions in this study are that teachers can apply the PjBL model to optimize student learning outcomes in other materials that are in accordance with the characteristics of the model and the PjBL learning model can be applied to biology learning with a wider scope of material.